Miejskie performanse Władysława Hasiora - Magdalena Figzał-Janikowska (Pamiętnik Teatralny, 2022)
This article discusses the performative art of Władysław Hasior, particularly his actions in the urban space. Initially expressed only in his artworks, since the 1970s Hasior’s need for dialogue with the spectator took the form of very expressive artistic manifestations involving audience participation, direct involvement of spectators in the creation of the performative event, and abolition of the distance between the artist and society. Due to the ontological status of these events, their ephemeral and fleeting nature, they have been the least explored area of Hasior’s work. The article analyzes his most important urban and open-air performances, such as the Procesja sztandarów (Banner Procession) in Łącko (1973), Solspann in Södertälje (1973–1976), and finally the ceremonial Przeprowadzka (Move) from the dormitory of Antoni Kenar school of fine arts to a new atelier in Zakopane (1984). These actions are considered in the context of contemporary discussions on participatory art: Claire Bishop’s antagonistic theory of participation and Grant H. Kester’s concept of dialogical art. It is argued that Hasior’s performative projects combined two strategies of participatory art; he was able to co-create ephemeral works together with the audience, while at the same time directing the spectators’ actions.